(untitled) (Transport systems and technologies, 2021)
The article presents a simulation model of a seaport grain terminal, created in the AnyLogic 8.5 PLE environment. The agent paradigm was chosen as the modeling paradigm, which allowed to adequately reproduce the process of interaction of road, rail and industrial transport in the process of grain processing. To this end, the main models-agents have been developed that interact with each other and form the overall technological process of grain processing by the marine terminal. The interaction of the created agents-models makes the logic of interaction of different types of transport and production and storage systems of the grain terminal of the seaport. On the basis of an experimental study of the grain terminal of the seaport in different technological conditions, its adequacy was confirmed taking into account the interaction of different modes of transport: main (sea, rail, road) and industrial transport of the grain terminal. For information support, an information-analytical part was created, the basis of which is a database of a simulation model of a grain terminal of a seaport with the appropriate software. The creation of a database of the grain terminal of the seaport provided the primary information of the simulation model; accumulation of information on the results of simulation experiments; the possibility of analytical study of the results of simulation experiments. The corresponding calculation of economic indicators of functioning of the export grain terminal is made on the basis of the accumulated data of simulation modeling by means of the developed software which has allowed to provide efficiency not only technological, but also economic decisions. The developed simulation model of the grain terminal of the seaport and its information-analytical part is in fact a system of decision support by the relevant services of the terminal in the conditions of variable information from customers, the presence of technological and natural risks.